The effect of layered double hydroxides on the vulcanisation and properties of elastomer compounds - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2025)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2025.